Thermoelectric power battery using al2o3 nanochannels of 10 nm diameter for energy harvesting of low-grade waste heat - Van Toan, Nguyen; Hasnan, Megat Muhammad Ikhsan Megat; Udagawa, Daiki; Inomata, Naoki; Toda, Masaya; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Ono, Takahito (Elsevier, 2019)
This work reports the effective of thermal-to-electric energy conversion based on a fluidic transport of nanochannels electrochemical devices induced by a temperature gradient. Using highly order periodic and high aspect ratio anodized aluminum oxide (AAO) nanochannels with 10 nm-diameter and 3 µm-length, the Slip effect and Soret diffusion inside the nanochannels drive large ion separation of monovalent KCl electrolyte between hot reservoir and cold reservoir respectively to generate power density of 255 µW cm−2 at temperature difference of 30 °C. This device has distinct advantages for conventional thermoelectrochemical energy harvester. They do not require the presence of constant temperature gradient in order to operate, they do not require an external voltage to charge and are solely charged by the presence of heat. The need for expensive redox couple are eliminated. High voltage generated by 3 order magnitude higher than TEC than contain no nanochannel device using same KCl electrolyte. They retain charge for extended period of time, up to 60% after 48 h, hence demonstrating their strong viability as a thermally driven integrated generator-storage device. The fundamental explanation for high performance device is due to the ability for the nanochannels to drive and retain charge polarization under a temperature gradient due to slip of nanochannels wall and Soret effect of the electrolyte. © 2019 Elsevier Ltd